Simulation Training in Penile Implant Surgery: Assessment of Surgical Confidence and Knowledge With Cadaveric Laboratory Training. Issue 4 (24th October 2018) - Lentz, Aaron C.; Rodríguez, Dayron; Davis, Leah G.; Apoj, Michel; Kerfoot, B. Price; Perito, Paul; Henry, Gerard; Jones, LeRoy; Carrion, Rafael; Mulcahy, John J.; Munarriz, Ricardo
Abstract: Introduction: Constraints on surgical resident training (work-hour mandates, shorter training programs, etc.) and availability of expert surgical educators may limit the acquisition of prosthetic surgical skills. As a result, training courses are being conducted to augment the prosthetic surgery learning experience. Aim: To evaluate the impact of a hands-on cadaver-based teaching program on resident procedural knowledge and procedural confidence with placement of a penile prosthesis. Main Outcome Measure: Changes in procedural knowledge and self-confidence following a focused training program on penile prosthetics. Methods: As part of the 2017 Society of Urologic Prosthetic Surgeons and the Sexual Medicine Society of North America Annual Meeting, 31 urology residents participated in a simulation lab in prosthetic urology. The lab included didactic lectures and a hands-on cadaveric laboratory. Participants completed surveys before and after the course. Wilcoxon Signed Rank tests for matched pairs were used to compare respondents' pre- and postcourse knowledge (% questions answered correctly) and confidence ratings. Prior implant experience was assessed. Results: 31 residents participated in this study. The majority of the participants were 4th- (41.9%) and 5th-year residents (38.7%). Participants showed a significant improvement in procedural knowledge test scores (68.8±13.4 vs 74.2 ± 13.0, P < .05) and self-reported increased median surgical confidence levels (4 vs 3, P  value < .001) after completion of the cadaveric course. Subgroup analysis demonstrated that residents with prosthetic surgery experience of <10 cases benefited the most. In addition, improvement in surgical confidence levels observed was greater than the improvement in surgical knowledge. The overall cost of the simulation training course was approximately $1, 483 per resident. Conclusion: Simulation training in prosthetic surgery seems to improve surgical confidence and knowledge. Further research is needed to better understand the benefits and limitations of simulation training.